Deep embrittlement and complete rupture of the lithosphere during the Mw 8.2 Tehuantepec earthquake. Issue 12 (December 2018) - Melgar, Diego; Ruiz-Angulo, Angel; Garcia, Emmanuel; Manea, Marina; Manea, Vlad.; Xu, Xiaohua; Ramirez-Herrera, M.; Zavala-Hidalgo, Jorge; Geng, Jianghui; Corona, Nestor; Pérez-Campos, Xyoli; Cabral-Cano, Enrique; et al.
Abstract Subduction zones, where two tectonic plates converge, are generally dominated by large thrust earthquakes. Nonetheless, normal faulting from extensional stresses can occur as well. Rare large events of this kind in the instrumental record have typically nucleated in and ruptured the top half of old and cold lithosphere that is in a state of extension driven by flexure from plate bending. Such earthquakes are limited to regions of the subducting slab cooler than 650 °C and can be highly tsunamigenic, producing tsunamis similar in amplitude to those observed during large megathrust events. Here, we show from analyses of regional geophysical observations that normal faulting during the moment magnitude Mw 8.2 Tehuantepec earthquake ruptured the entire Cocos slab beneath the megathrust region. We find that the faulting reactivated a bend-fault fabric and ruptured to a depth well below the predicted brittle–ductile transition for the Cocos slab, including regions where temperature is expected to exceed 1, 000 °C. Our findings suggest that young oceanic lithosphere is brittle to greater depths than previously assumed and that rupture is facilitated by wholesale deviatoric tension in the subducted slab, possibly due to fluid infiltration. We conclude that lithosphere can sustain brittle behaviour and fail in an earthquake at greater temperatures and ages than previously considered. Geophysical observations of the 2017 Tehuantepec earthquake suggest that oceanic lithosphere can sustain brittle behaviour and rupture in an earthquake at greater depths than previously assumed.